PROGRAM MBKM ASISTENSI MENGAJAR: PENGGOLONGAN AKUN PERUSAHAAN JASA DI SMA SANTA URSULA JAKARTA - Darwis, Andrea Stephanie; Susanti, Merry (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2024)
This article provides an explanation of the Merdeka Belajar Kampus Merdeka (MBKM) program for teaching assistance in classifying accounts for service companies at Santa Ursula High School in Jakarta. Based on the author’s observations, the partner school has implemented the Merdeka Curriculum in accordance with Regulation of the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia Number 12 of 2024 concerning the Curriculum for Early Childhood Education, Elementary Education, and Secondary Education. The Merdeka curriculum brings new challenges for students, particularly those in the 11th grade, in learning accounting as an elective subject, which had not been introduced in the previous grade (10th grade). Therefore, the MBKM teaching assistance program, involving students from the Accounting Department at Tarumanagara University (UNTAR), is expected to help overcome these difficulties. The program aims to broaden the students’ knowledge through teaching experiences outside the classroom, strengthen their understanding of accounting concepts, and provide an opportunity to share knowledge with Santa Ursula High School students. The teaching method involves creating learning materials that simplify the students' understanding of accounting through Q&A sessions, discussions, and problem-solving simulations. The outcome of the MBKM program includes review materials on account classification to be used as teaching aids. Through this program, UNTAR accounting students can develop practical and theoretical skills, while Santa Ursula High School students are expected to gain a better understanding of accounting, preparing them to face future accounting learning challenges. ABSTRAK Artikel ini memberikan penjelasan mengenai program Merdeka Belajar Kampus Merdeka (MBKM) atas asistensi mengajar penggolongan akun perusahaan jasa di Sekolah Menengah Atas (SMA) Santa Ursula Jakarta. Berdasarkan hasil observasi penulis, mitra sekolah telah menerapkan Kurikulum Merdeka sesuai Peraturan Menteri Pendidikan, Kebudayaan, Riset, dan Teknologi (Permendikbudristek) Republik Indonesia Nomor 12 Tahun 2024 tentang Kurikulum pada Pendidikan Anak Usia Dini, Jenjang Pendidikan Dasar, dan Jenjang Pendidikan Menengah. Kurikulum merdeka membawa tantangan baru bagi para siswi, khususnya kelas XI, dalam mempelajari mata pelajaran pilihan akuntansi yang belum pernah diperkenalkan pada mata pelajaran sebelumnya di kelas X. Maka dari itu, program MBKM asistensi mengajar yang melibatkan mahasiswa/i program studi Akuntansi dari Universitas Tarumanagara (UNTAR) diharapkan dapat membantu mengatasi kesulitan tersebut. Program ini bertujuan untuk menambah wawasan mahasiswa/i melalui pengalaman mengajar di luar kelas, memperkuat pemahaman terhadap konsep akuntansi, serta memberikan kesempatan untuk berbagi pengetahuan dengan siswi SMA Santa Ursula. Metode pelaksanaan kegiatan mengajar ini melibatkan penyusunan media pembelajaran yang mempermudah pemahaman akuntansi para siswi melalui tanya jawab, diskusi, dan simulasi pengerjaan soal. Hasil dari program MBKM berupa materi peninjauan ulang penggolongan akun sebagai bahan ajar. Melalui program ini, mahasiswa/i akuntansi UNTAR dapat mengembangkan keterampilan praktis dan teoritis, sementara para siswi SMA Santa Ursula diharapkan memperoleh pemahaman yang lebih baik tentang akuntansi, sehingga siap menghadapi tantangan pembelajaran akuntansi di masa mendatang